Dietary nitrate supplementation improves team sport-specific intense intermittent exercise performance - Wylie, L. J.; Mohr, M.; Krustrup, P.; Jackman, S. R.; Ermidis, G.; Kelly, J.; Black, M. I.; Bailey, S. J.; Vanhatalo, A.; Jones, A. M (European Journal of Applied Physiology, 2013)
Recent studies have suggested that dietary inorganic nitrate (NO3 -) supplementation may improve muscle efficiency and endurance exercise tolerance but possible effects during team sport-specific intense intermittent exercise have not been examined. We hypothesized that NO3 - supplementation would enhance high-intensity intermittent exercise performance. Fourteen male recreational team-sport players were assigned in a double-blind, randomized, crossover design to consume 490 mL of concentrated, nitrate-rich beetroot juice (BR) and nitrate-depleted placebo juice (PL) over ~30 h preceding the completion of a Yo-Yo intermittent recovery level 1 test (Yo-Yo IR1). Resting plasma nitrite concentration ([NO2 -]) was ~400 % greater in BR compared to PL. Plasma [NO2 -] declined by 20 % in PL (P < 0.05) and by 54 % in BR (P < 0.05) from pre-exercise to end-exercise. Performance in the Yo-Yo IR1 was 4.2 % greater (P < 0.05) with BR (1,704 ± 304 m) compared to PL (1,636 ± 288 m). Blood [lactate] was not different between BR and PL, but the mean blood [glucose] was lower (3.8 ± 0.8 vs. 4.2 ± 1.1 mM, P < 0.05) and the rise in plasma [K+] tended to be reduced in BR compared to PL (P = 0.08). These findings suggest that NO3 - supplementation may promote NO production via the nitrate-nitrite-NO pathway and enhance Yo-Yo IR1 test performance, perhaps by facilitating greater muscle glucose uptake or by better maintaining muscle excitability. Dietary NO3 - supplementation improves performance during intense intermittent exercise and may be a useful ergogenic aid for team sports players.